Tekanan Stakeholder dan Ukuran Perusahaan pada Sustainability Report - Darmawan, Bagus Adya; Sudana, I Putu (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
The research aims to determine the effect of stakeholder pressure and company size on the Sustainability Report. The research was conducted at the Indonesia Stock Exchange (IDX) using the 2017-2020 research period. The population in the research is all companies listed on the IDX in 2017-2020 which issued Sustainability Reports and used the GRI Standards. The number of samples used were 84 observations. In this research using non-probability sampling method with purposive sampling technique. Research using multiple linear analysis. The research results show that environmental pressure and company size have a positive effect on Sustainability Report, employee pressure and shareholder pressure have no effect on Sustainability Report and consumer pressure has a negative effect on Sustainability Report. Keywords: Sustainability Report; Stakeholder Pressure; Company Size.